Existence and Non-existence of Global Solutions of a Degenerate Parabolic System with Nonlinear Boundary Conditions (Journal of Partial Differential Equations, 2004)
In this paper, we study the non-negative solutions to a degenerate parabolic system with nonlinear boundary conditions in the multi-dimensional case. By the upper and lower solutions method, we give the conditions on the existence and non-existence of global solutions.
Keywords: Degenerate parabolic system; global solution; blow-up in finite time